2020
DOI: 10.1553/populationyearbook2020.int01
|View full text |Cite
|
Sign up to set email alerts
|

Introduction: the relevance of studying fertility across time and space

Abstract: the sharing, use and adaptation in any medium, provided that the user gives appropriate credit, provides a link to the license, and indicates if changes were made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Often considered frontrunners in implementing family-friendly policies, the Nordic countries have traditionally had relatively high fertility levels compared to other European nations (Sobotka 2020). The factors that have contributed to the recent fertility declines in the Nordic countries are not yet fully understood, especially given the lack of substantial changes to family policies .…”
Section: Birthsmentioning
confidence: 99%

State of the Nordic Region 2024

Norlén,
Heleniak,
Sánchez Gassen
et al. 2024
“…Often considered frontrunners in implementing family-friendly policies, the Nordic countries have traditionally had relatively high fertility levels compared to other European nations (Sobotka 2020). The factors that have contributed to the recent fertility declines in the Nordic countries are not yet fully understood, especially given the lack of substantial changes to family policies .…”
Section: Birthsmentioning
confidence: 99%

State of the Nordic Region 2024

Norlén,
Heleniak,
Sánchez Gassen
et al. 2024
“…On the aggregate level, some studies have demonstrated that a two-child family ideal has been persistent in most European countries and in the US over the last three decades (Hagewen and Morgan 2005;Sobotka and Beaujouan 2014), suggesting that the ideal number of children has stabilized around the replacement level. Fertility rates, however, have been declining to well-below replacement levels in most high-income countries today (Sobotka 2020). This macro-level disparity between ideal and achieved average family size has been described as a 'fertility gap' (Philipov 2009).…”
Section: Introductionmentioning
confidence: 99%